A hydrophobic fumed nano-silica and its preparation method and application
Chemical grafting reaction and compression kneading are carried out through the twin-screw mixing process, which solves the defects of traditional hydrophobic gas-phase nanosilicon dioxide in construction properties, tap density and filling performance, and achieves the effects of high tap density and high filling ratio.
Patent Information
- Application Number
- CN202411782733.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-06
AI Technical Summary
Traditional surface hydrophobic treatment of gas-phase nanosilicon dioxide has defects in construction properties, tap density, transportation and storage costs, as well as filling ratios and reinforcement properties.
The chemical grafting reaction and compression kneading are carried out using the twin-screw mixing process, and the nano powder is agglomerated and opened by high shear force, exposing the internal hydroxyl groups, and grafted with the surface treatment agent, thereby increasing the tap density and filling ratio.
A gas-phase nanosilicon dioxide with high tap density is achieved, which improves constructionability and transparency, reduces transportation and storage costs, and enhances filling ratio and reinforcement performance.
Smart Images

Figure CN119242074B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to hydrophobic gas-phase nano silicon dioxide and a preparation method and application thereof, belonging to the technical field of powder processing and preparation. Background Art
[0002] Fumed nano-silica is obtained by high-temperature pyrolysis of chlorosilane in a mixed atmosphere of hydrogen and oxygen. Due to its small particle size and large specific surface area, it is widely used in resin thickeners, matting agents, reinforcing agents, cosmetics, toners and other fields. A large number of silanol groups remain on the surface of silica prepared by pyrolysis, showing hydrophilic and oleophobic properties. In many application scenarios, hydrophobic treatment is required first to reduce the interaction between primary particles, thereby improving the wettability between fumed nano-silica and organic molecules, and improving the dispersibility of particles and the comprehensive performance of materials.
[0003] However, the traditional surface hydrophobic treated fumed nano-silica, like the hydrophilic fumed nano-silica, maintains a relatively low tap density and has the following disadvantages during use: first, poor construction performance, difficult to operate and easy to generate dust during application; second, low tap density inevitably leads to high transportation and storage costs; third, the thickening property is too strong to meet high filling requirements, and other reinforcing agents are required to be used in combination in many systems, and other reinforcing agents often greatly reduce the transparency of the system.
[0004] U.S. Patent No. US4877595A discloses a method for preparing silicic acid by pyrolysis. This method removes air from the gaps in the powder through vacuum compression, which can effectively increase the tap density of gas silicon and solve the dust problem, but it cannot increase the filling ratio and reinforcement performance of gas silicon. Summary of the invention
[0005] The object of the present invention is to provide a hydrophobic gas-phase nano-silica and a preparation method and application thereof, so as to solve the technical problems existing in the prior art as described above.
[0006] The technical solution provided by the present invention is as follows:
[0007] One of the purposes of the present invention is to provide a method for preparing hydrophobic fumed nano-silica, comprising the following steps:
[0008] S1: preheating the kneading and heating section of the twin-screw equipment;
[0009] S2: conveying the hydrophilic fumed nano-silica and the surface treatment agent to the conveying section of the twin-screw equipment for preliminary mixing;
[0010] S3: The preliminarily mixed powder is then transported to the kneading and heating section of the twin-screw equipment for chemical grafting reaction and compression kneading.
[0011] On the basis of the above technical solution, the present invention can also be improved as follows:
[0012] Furthermore, the preheating temperature in step S1 is 50-300° C. Preferably, the preheating temperature is 80-150° C.
[0013] Furthermore, in step S2, the weight of the surface treatment agent accounts for 5-30% of the hydrophilic fumed nano-silica. Preferably, the weight of the surface treatment agent accounts for 8-20% of the hydrophilic fumed nano-silica.
[0014] Furthermore, the surface treatment agent in step S2 is silazane and / or organosilane.
[0015] Furthermore, the silazane is hexamethyldisilazane; the organosilane includes but is not limited to dimethyldichlorosilane, γ-methacryloxypropyltrimethoxysilane, and vinyltrimethoxysilane; the organosilane has the following structure:
[0016]
[0017] Wherein R1, R2, and R3 are any one of the following groups: halo (Cl, Br), alkyl (such as methyl, ethyl, n-propyl, isopropyl, butyl, isobutyl, etc.), cycloalkyl, alkoxy (such as methoxy, ethoxy, propoxy, etc.).
[0018] m is any value between 0 and 20.
[0019] R 4 Any of the following groups: methyl, vinyl, methacryloyloxy, alkoxy (such as methoxy, ethoxy, propoxy, etc.), aryl (such as phenyl, phenyl containing a substituent), -C 4 F 9 、-OCF 2 -CHF-CF 3 , C 6 F 13 、-O-CF 2 -CHF 2 、-NH 2 、-N 3 、-SCN、-NH-CH 2 -CH 2 -NH 2 、-N-(CH 2 -CH 2 -NH 2 ) 2 、-OOC(CH 3 )C=CH 2 、-OCH 2 -CH(O)CH2 、-NH-CO-N-CO-(CH 2 ) 5 、-NH-COO-CH 3 、-NH-COO-CH 2 -CH 3 、-NH-(CH 2 ) 3 Si(OR) 3 (where R is an alkyl group), -S x -(CH 2 ) 3 Si(OR) 3 (wherein x is 1-2, R is an alkyl group), -SH.
[0020] Furthermore, the twin-screw equipment adopts ceramic sleeves and ceramic elements.
[0021] Furthermore, the specific surface area of the hydrophilic fumed nano-silica is 40-380 m 2 / g.
[0022] Furthermore, the method for preparing hydrophobic fumed nano-silica further comprises step S4: conveying the compressed and kneaded powder through the discharge port of the twin-screw equipment via a pneumatic conveying pipeline to a packaging barrel for packaging.
[0023] The second object of the present invention is to provide a hydrophobic fumed nano-silica, which is prepared by the above-mentioned preparation method of the hydrophobic fumed nano-silica.
[0024] The third object of the present invention is to provide an application of the hydrophobic fumed nano-silica in the preparation of organic silicone rubber elastomer.
[0025] Compared with the prior art, the technical solution provided by the present invention has the following beneficial effects:
[0026] The present invention adopts a twin-screw mixing process to achieve compression of fumed nano-silicon dioxide in a twin-screw device to achieve a high tap density. The conventional tap density of fumed silicon dioxide is 60 g / L, while the tap density of the present invention can reach 200-300 g / L after twin-screw treatment, which reduces the space occupied during packaging and transportation, improves construction performance and reduces dust during later use;
[0027] The extrusion force and shear force generated by the twin-screw equipment of the present invention are completely different from the high pressure of the existing high-temperature and high-pressure reactor. The torque of the twin-screw equipment used in the present invention can easily reach more than 4000N·m. The present invention needs to use high shear force to open the agglomeration of nanopowders so that the internal hydroxyl groups are exposed to achieve the effects of high filling, high reinforcement and high transparency. However, the stirring shear force of the high-temperature and high-pressure reactor is limited. The torque of the stirring paddle of the industrial stirring reactor does not exceed 500N·m. In addition, the high-temperature and high-pressure reactor has the problem of sealing. High pressure can only be achieved by filling the sealed reactor with high-pressure gas. The high-temperature and high-pressure reactor is usually not used for pure solid-phase reaction systems. Solvents need to be added to the reactor. The application direction is solvent thermal reaction, hydrothermal reaction, etc. If the high-temperature and high-pressure reactor is used for pure powder processing, since the powder will generate dust, no matter where the sealing element is, it can be foreseen that the powder will block the sealing element. The sleeve design of the twin-screw equipment used in the present invention is integrated, and since there is no airtightness requirement, there is no problem of powder blocking the sealing element.
[0028] In the shearing and kneading process of the twin screws, the nano-particle agglomerates of the hydrophilic fumed nano-silica are opened, and the hidden hydroxyl groups between the particles are exposed, and then grafted with the surface treatment agent to better eliminate the residual hydroxyl groups, thereby making the polarity of the hydrophobic fumed nano-silica and the substrate more compatible in the field of adhesives and rubbers, and having higher transparency;
[0029] Due to the interaction between the nanoparticles such as van der Waals force and electrostatic adsorption, the particles are agglomerated and difficult to separate. During use, it is usually necessary to disperse the fumed silica by a dispersion disk, ball mill or other dispersion methods. The process of the present invention forcibly disperses the adsorbed nanoparticles through the strong shearing effect of the twin screws, and then performs hydrophobic chemical grafting. The grafted powder is no longer strongly adsorbed together due to the steric hindrance of the chemical groups. During use, it can be evenly dispersed in the matrix, more compatible with the polarity of the matrix, with higher transparency and higher filling ratio. The high-temperature reactor used in the conventional process does not have a strong shearing effect, and cannot disperse the adsorbed hydrophilic fumed silica, and the adsorption surface between the nanoparticles cannot be modified by chemical grafting.
[0030] In addition, during the compression and kneading process, the twin-screw equipment heats the hydrophobic gas-phase nano-silicon dioxide powder at the same time, and the compressed powder can be directly packaged to achieve continuous production; the high-temperature reactor used in conventional processes is batch production, while the twin-screw used in the present invention can continuously feed and discharge materials to achieve continuous production.
[0031] The twin-screw equipment of the present invention avoids the problem of metal wear pollution caused by friction by using ceramic materials to make the sleeve and the kneading element. At the same time, heating treatment can be performed in the kneading stage, thereby realizing a continuous mixing production process. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is the SEM image of the sample prepared in Example 1;
[0033] Figure 2 This is the SEM image of the sample prepared in Comparative Example 1. DETAILED DESCRIPTION
[0034] The principles and features of the present invention are described below in conjunction with examples. The examples are only used to explain the present invention and are not used to limit the scope of the present invention.
[0035] Example 1
[0036] A method for preparing hydrophobic fumed nano-silica comprises the following steps:
[0037] S1: preheat the kneading heating section of the twin-screw equipment to 120°C;
[0038] S2: The feed system of the twin screw extruder feeds a surface area of 300m 2 / g of hydrophilic fumed nano-silica, γ-methacryloxypropyltrimethoxysilane accounting for 10% of the mass of the hydrophilic fumed nano-silica, and hexamethyldisilazane accounting for 5% of the mass of the hydrophilic fumed nano-silica are transported to the conveying section of the twin-screw equipment for preliminary mixing;
[0039] S3: The preliminarily mixed powder is then transported to the kneading and heating section of the twin-screw equipment for chemical grafting reaction and compression kneading;
[0040] S4: The compressed and kneaded powder is transported to the packaging barrel through the discharge port of the twin-screw equipment and the pneumatic conveying pipeline for packaging to achieve continuous production.
[0041] Example 2
[0042] A method for preparing hydrophobic fumed nano-silica comprises the following steps:
[0043] S1: Preheat the kneading and heating section of the twin-screw equipment to 80°C. The other steps are the same as in Example 1.
[0044] Example 3
[0045] A method for preparing hydrophobic fumed nano-silica comprises the following steps:
[0046] S1: preheat the kneading and heating section of the twin-screw equipment to 150°C. The other steps are the same as in Example 1.
[0047] Example 4
[0048] A method for preparing hydrophobic fumed nano-silica comprises the following steps:
[0049] S1: preheat the kneading heating section of the twin-screw equipment to 120°C;
[0050] S2: The feed system of the twin screw extruder feeds a surface area of 300m 2 / g of hydrophilic fumed nano-silica and hexamethyldisilazane accounting for 10% of the mass of the hydrophilic fumed nano-silica are transported to the conveying section of the twin-screw equipment for preliminary mixing;
[0051] S3: The preliminarily mixed powder is then transported to the kneading and heating section of the twin-screw equipment for chemical grafting reaction, compression and kneading;
[0052] S4: The compressed and kneaded powder is transported to the packaging barrel through the discharge port of the twin-screw equipment and the pneumatic conveying pipeline for packaging to achieve continuous production.
[0053] Example 5
[0054] A method for preparing hydrophobic fumed nano-silica comprises the following steps:
[0055] S1: Preheat the kneading and heating section of the twin-screw equipment to 80°C. The other steps are the same as those in Example 4.
[0056] Example 6
[0057] A method for preparing hydrophobic fumed nano-silica comprises the following steps:
[0058] S1: Preheat the kneading and heating section of the twin-screw equipment to 150° C. The other steps are the same as those in Example 4.
[0059] Example 7
[0060] A method for preparing hydrophobic fumed nano-silica comprises the following steps:
[0061] S1: preheat the kneading heating section of the twin-screw equipment to 120°C;
[0062] S2: The feed system of the twin screw extruder feeds a surface area of 300m 2 / g of hydrophilic fumed nano-silica and octyltriethoxysilane accounting for 10% of the mass of the hydrophilic fumed nano-silica are transported to the conveying section of the twin-screw equipment for preliminary mixing;
[0063] S3: The preliminarily mixed powder is then transported to the kneading and heating section of the twin-screw equipment for chemical grafting reaction, compression and kneading;
[0064] S4: The compressed and kneaded powder is transported to the packaging barrel through the discharge port of the twin-screw equipment and the pneumatic conveying pipeline for packaging to achieve continuous production.
[0065] Example 8
[0066] A method for preparing hydrophobic fumed nano-silica comprises the following steps:
[0067] S1: Preheat the kneading and heating section of the twin-screw equipment to 80°C. The other steps are the same as in Example 7.
[0068] Example 9
[0069] A method for preparing hydrophobic fumed nano-silica comprises the following steps:
[0070] S1: Preheat the kneading and heating section of the twin-screw equipment to 150°C. The other steps are the same as in Example 7.
[0071] Example 10
[0072] A method for preparing hydrophobic fumed nano-silica comprises the following steps:
[0073] S1: preheat the kneading heating section of the twin-screw equipment to 120°C;
[0074] S2: The feed system of the twin screw extruder feeds a surface area of 300m 2 / g of hydrophilic fumed nano-silica and dimethyldichlorosilane accounting for 10% of the mass of the hydrophilic fumed nano-silica are transported to the conveying section of the twin-screw equipment for preliminary mixing;
[0075] S3: The preliminarily mixed powder is then transported to the kneading and heating section of the twin-screw equipment for chemical grafting reaction, compression and kneading;
[0076] S4: The compressed and kneaded powder is transported to the packaging barrel through the discharge port of the twin-screw equipment and the pneumatic conveying pipeline for packaging to achieve continuous production.
[0077] Embodiment 11
[0078] A method for preparing hydrophobic fumed nano-silica comprises the following steps:
[0079] S1: Preheat the kneading and heating section of the twin-screw equipment to 80°C. The other steps are the same as in Example 10.
[0080] Example 12
[0081] A method for preparing hydrophobic fumed nano-silica comprises the following steps:
[0082] S1: Preheat the kneading and heating section of the twin-screw equipment to 150°C. The other steps are the same as in Example 10.
[0083] Comparative Example 1
[0084] Referring to the process steps in Chinese patent CN101755017A; spray γ-methacryloxypropyltrimethoxysilane accounting for 10% of the mass of the gas silicon and hexamethyldisilazane accounting for 5% of the mass of the gas silicon onto the surface of the gas silicon, and heat treat at 150°C for 2h.
[0085] Comparative Example 2
[0086] Refer to the process steps in Chinese patent CN101755017A; spray hexamethyldisilazane accounting for 10% of the mass of the gas silicon onto the surface of the gas silicon, and heat treat at 150°C for 2h.
[0087] Comparative Example 3
[0088] Refer to the process steps in Chinese patent CN101755017A; spray 10% of the mass of the gas silicon with octyltriethoxysilane onto the surface of the gas silicon, and heat treat at 150°C for 2h.
[0089] Comparative Example 4
[0090] Refer to the process steps in Chinese patent CN101755017A; spray 10% of dimethyldichlorosilane by mass of gas silicon onto the surface of gas silicon, and heat treat at 150°C for 2h.
[0091] Preparation Example
[0092] The hydrophobic gas-phase nano-silica prepared in Examples 1-12 and Comparative Examples 1-4 is prepared into a silicone rubber elastomer gasket, comprising the following steps: using a linear vinyl silicone oil with a vinyl content of 0.018 mol / 100 g and a side chain hydrogenated silicone oil of 0.18 mol / 100 g, in a mass ratio of 1:1, a hydrophobic gas-phase nano-silica filling rate of 30%, a Pt catalyst (Karstedt catalyst, Pt content 3000 ppm) of 0.02%, and an inhibitor (ethynyl cyclohexanol) of 0.002%, and thermally curing to prepare a silicone rubber elastomer gasket.
[0093] The performance tests were performed on the hydrophobic fumed nano-silica prepared in Examples 1-12 and Comparative Examples 1-4:
[0094] 1. Tap density: tested with a tap density meter;
[0095] 2. Hydrophobicity: Take 0.2g of hydrophobic fumed nano-silica and add it to 50g of deionized water. Add methanol while stirring until the hydrophobic fumed nano-silica is completely wetted by the methanol-water mixture. Record the mass percentage of methanol in the methanol-water solution as the hydrophobicity of the hydrophobic fumed nano-silica.
[0096] 3. Carbon content: tested with a carbon-sulfur analyzer;
[0097] 4. Specific surface area: tested using BET method and specific surface area tester;
[0098] 5.SEM image: The test was performed using a scanning electron microscope.
[0099] The performance test of the organosilicon rubber elastomer gasket prepared from the hydrophobic fumed nano-silica prepared in Examples 1-12 and Comparative Examples 1-4 was performed:
[0100] 1. Filling rate: The filling rate is the proportion of hydrophobic fumed nano-silica used when the slurry viscosity is 200000mPa*s (Brookfield viscometer DV2T, 96# rotor, 6rpm speed);
[0101] 2. Transparency: Visible light spectrophotometer, using silicone gaskets without fumed silica as the comparison standard, to test relative transparency;
[0102] 3. Tear strength: Tested using a tensile testing machine, refer to GB-T529-2008;
[0103] 4. Elongation at break: Tested using a tensile testing machine, with reference to GBT528-2009.
[0104] The test results are shown in Table 1. Figure 1 and Figure 2 As shown:
[0105] Table 1 Performance test results
[0106]
[0107] It can be concluded from Table 1 that by comparing Examples 1, 2, and 3 with Comparative Example 1, Examples 4, 5, and 6 with Comparative Example 2, Examples 7, 8, and 9 with Comparative Example 3, and Experimental Examples 10, 11, and 12 with Comparative Example 4, it can be seen that under the same modifier treatment, the filling rate of the organic silicone rubber elastomer gasket prepared by the hydrophobic fumed nano-silica prepared by the present invention can reach about 30% when the slurry with a viscosity of 200,000 mPa*s is modulated, which is significantly higher than the comparative example; at the same time, compared with the comparative example, the organic silicone rubber elastomer gasket prepared by the hydrophobic fumed nano-silica prepared by the present invention has higher transparency, greater tear strength, and higher elongation at break.
[0108] This shows that the use effect of the twin-screw device of the present invention cannot be achieved by using a heatable mixer such as a plowshare mixer, a high-temperature reactor, etc. in the comparative example, while the use of the twin-screw device of the present invention achieves the effects of high filling, high reinforcement, and high transparency.
[0109] The hydrophobic fumed nano-silica prepared by using different surface treatment agents in the present invention has different transparency at a filling rate of about 30%. The transparency of the silicone rubber elastomer gasket prepared by using dimethyldichlorosilane as the surface treatment agent is as low as 15%, and the transparency of the silicone rubber elastomer gasket prepared by using γ-methacryloxypropyltrimethoxysilane and hexamethyldisilazane, hexamethyldisilazane, and octyltriethoxysilane as the surface treatment agents can reach about 40%.
[0110] Figure 1 This is the SEM image of the sample prepared in Example 1. Figure 1 It can be seen that the hydrophobic fumed silica prepared by the twin-screw process of Example 1 of the present invention is in a soft agglomerated state, and the twin-screw extrusion produces a granulation effect so that the tap density of the fumed silica is significantly improved.
[0111] Figure 2 The SEM image of the sample prepared in Comparative Example 1 is Figure 2 It can be seen that the hydrophobic fumed silica prepared by the conventional process in Comparative Example 1 maintains the state of the original powder, and the fumed silica powder presents a loose structure and a low tap density.
[0112] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing hydrophobic fumed nano-silica, characterized in that: The following steps are involved: S1: preheating the kneading and heating section of the twin-screw equipment; S2: conveying the hydrophilic fumed nano-silica and the surface treatment agent to the conveying section of the twin-screw equipment for preliminary mixing; S3: The preliminarily mixed powder is then transported to the kneading and heating section of the twin-screw equipment for chemical grafting reaction and compression kneading; Wherein, the preheating temperature in step S1 is 50-300°C, In step S2, the weight of the surface treatment agent accounts for 5-30% of the hydrophilic fumed nano-silica. The surface treatment agent in step S2 is silazane and / or organosilane, The silazane is hexamethyldisilazane; the organosilane has the following structure: Wherein, R1, R2, and R3 are any one of the following groups: halo, alkyl, cycloalkyl, and alkoxy; m is any value between 0 and 20; R4 is any one of the following groups: methyl, vinyl, methacryloyloxy, alkoxy, aryl, -C4F9, -OCF2-CHF-CF3, C6F 13 , -O-CF2-CHF2, -NH2, -N3, -SCN, -NH-CH2-CH2-NH2, -N-(CH2-CH2-NH2)2, -OOC(CH3)C=CH2, -OC H2-CH(O)CH2, -NH-CO-N-CO-(CH2)5, -NH-COO-CH3, -NH-COO-CH2-CH3, -NH-(CH2)3Si(OR)3, -S x -(CH2)3Si(OR)3, -SH, wherein R is an alkyl group and x is 1-2.
2. The method for preparing hydrophobic fumed nano-silica according to claim 1, characterized in that: The twin-screw equipment adopts ceramic sleeves and ceramic elements.
3. The method for preparing hydrophobic fumed nano-silica according to claim 1, characterized in that: The specific surface area of the hydrophilic gas-phase nano-silica is 40-380 m2 / g.
4. The method for preparing hydrophobic fumed nano-silica according to claim 1, characterized in that: The method further comprises step S4: conveying the compressed and kneaded powder through the discharge port of the twin-screw device via a pneumatic conveying pipeline to a packaging barrel for packaging.
5. A hydrophobic fumed nano-silica, characterized in that: The hydrophobic fumed nano-silica is prepared by the preparation method according to any one of claims 1 to 4.
6. Use of the hydrophobic fumed nano-silica as claimed in claim 5 in the preparation of organic silicone rubber elastomer.
Citation Information
Patent Citations
Surface-modified, pyrogenically prepared silicas
CN101755017A
Method of compressing pyrogenically prepared silicic acid
US4877595A
Modified fumed silica with flattened structure and high tap density as well as preparation method and application of modified fumed silica
CN113105758A
Method for modifying silicon dioxide through plasma in-situ polymerization silicone oil and application
CN115806746A
Process for preparing silicone rubber matrix composition
CN116438227A